Excel 2013 for Biological and Life Sciences Statistics : A Guide to Solving Practical Problems - Quirk, Thomas J.; Quirk, Meghan; Horton, Howard F. (Excel for Statistics, 2015)
This is the first book to show the capabilities of Microsoft Excel to teach biological and life sciences statistics effectively.  It is a step-by-step exercise-driven guide for students and practitioners who need to master Excel to solve practical science problems.  If understanding statistics isn't your strongest suit, you are not especially mathematically-inclined, or if you are wary of computers, this is the right book for you.  Each chapter explains statistical formulas and directs the reader to use Excel commands to solve specific, easy-to-understand science problems.  Practice problems are provided at the end of each chapter with their solutions in an appendix.  Separately, there is a full Practice Test (with answers in an Appendix) that allows readers to test what they have learned.  Includes 164 illustrations in color Suitable for undergraduates or graduate student Prof. Tom Quirk is currently a Professor of Marketing at The Walker School of Business and Technology at Webster University in St. Louis, Missouri (USA).  He has published over 20 articles in professional journals, and presented more than 20 papers at professional conferences.  He holds a B.S. in Mathematics from John Carroll University, both an M.A. in Education and a Ph.D. in Educational Psychology from Stanford University, and an MBA from the University of Missouri-St. Louis.  Dr. Meghan H. Quirk holds both a Ph.D. in Biological Education and an M.A. in Biological Sciences from the University of Northern Colorado (UNC) and a B.A. in Biology and Religion from Principia College in Elsah, Illinois.  She has done research on foodweb dynamics at Wind Cave National Park in South Dakota and research in agro-ecology in Southern Belize.  She has co-authored an article on shortgrass steppe ecosystems in Photochemistry & Photobiology.  She was a National Science Foundation Fellow GK-12, and currently teaches in Bailey, Colorado.  Howard F. Horton holds an M.S. in Biological Sciences from the University of Northern Colorado (UNC) and a B.S. in Biological Sciences from Mesa State College.  He has worked on research projects in Pawnee National Grasslands, Rocky Mountain National Park, Long-Term Ecological Research at Toolik Lake, Alaska, and Wind Cave, South Dakota.  He has co-authored articles in The International Journal of Speleology  and The Journal of Cave and Karst Studies. He was a National Science Foundation Fellow GK-12, and a District Wildlife Manager with the Colorado Division of Parks and Wildlife.  He is currently the Angler Outreach Coordinator with the Colorado Parks and Wildlife (USA).